Long‐term memory retention in a wild fish species “Labroides dimidiatus” eleven months after an aversive event - Triki, Zegni; Bshary, Redouan (My University, 2019)
Memory is essential to enhance future survival and reproduction as it helps in storing and retrieving useful information to solve particular environmental problems. However, we lack quantitative evidence on how far animals in the wild can maintain given information for extended periods without reinforcement. Here, we document correlative evidence of cleaner fish Labroides dimidiatus remembering being caught in a barrier net for up to 11 months. In 2015, about 60% of cleaners from one large isolated reef had been used for laboratory experiments and then returned to their site of capture. Eleven months later, 50% of cleaners at the same site showed an unusual hiding response to the placement of the barrier net, in contrast to three control sites where no cleaners had been caught during the last 2 years. The results suggest that a single highly aversive event (i.e., being caught in a barrier net) resulted in cleaners storing long‐term crucial information that allowed them to avoid being caught again. Our results further our knowledge of fish cognitive capacities and long‐term memory retention.
Keywords: cognition; escape behaviour; female cleaner fish; learning; memory retention